Architecture follows nature : biomimetic principles for innovative design - Mazzoleni, Ilaria; Price, Shauna (Boca Raton : CRC Press, 2013)
"Biology influences design projects in many ways; the related impact is known as biomimetics or biomimicry. Investigating the animal kingdom as a source of inspiration, this book focuses on the analysis of various animal skins, translating the learned principles into the built environment. Skin is a complex organ that performs various functions; similarly, building envelopes serve multiple roles as interfaces between building inhabitants and environmental elements. The resulting architectural building coverings take into consideration dynamic local environmental conditions. The text illustrates how supporting biomimetic principles can create a more sustainable way of building and living"--
Includes bibliographical references (pages 211-227) and index.
ARC
Keywords: Architecture and biology; Architectural design; Biomimicry; SCIENCE / Life Sciences / Evolution; TECHNOLOGY & ENGINEERING / Industrial Health & Safety